Employers and the Welfare state: the political economic organization of firms and social policy in contemporary capitalist democracies - Swank, Duane; Martin, Cathie Jo (2001)
lhe authors argue that the organization of employers shapes society policy support among firms and, in turn, affects social policy outcomes. Specifically, the authors argue that the centralization and cohension of employer groups and economic cooperation across enterprises positively affects social welfare provision. Empirically, the authors assess the impacts of business organization on social welfare effort in 15 developed democracies between the 1970s and 1990s; the authors also provide analysis of the impact of employer organization on active labor market policy. The authors find that the organization of employers is one of the most important determinants of overall social welfare effort. The authors also find that employer organization affects the development of active labor market policies, and it influences the degree to which social democratic parties pursue active labor market programs. The authors conclude with a discussion of the findings' implications for theories of social corporatism and the welfare state. - Reproduced.
Keywords: Social policy